Burden of Atopic Dermatitis in Swedish Adults: A Population-based Study - Grigorios Theodosiou; Scott Montgomery; Alexandra Metsini; Florence J. Dalgard; Åke Svensson; Laura B. Kobyletzki (Medical Journals Sweden, 2019)
The burden of atopic dermatitis (AD) was assessed. A population-based, cross-sectional questionnaire study was performed among 34,313 Swedish adults in 2017. The prevalence of AD was 14%. Adults with mild AD had an increased relative risk ratio (RRR) of severe depression (aRRR 1.78, 95% confidence interval (95% CI) 1.50-2.12) and anxiety (aRRR 1.97, 95% CI 1.69-2.30), which was higher for severe AD (aRRR 6.22 95% CI 4.60- 8.42, aRRR 5.62 95% CI 4.10-7.71, respectively). Persons with severe AD were less likely to have a university degree (aRRR 0.55, 95% CI 0.34-0.90) and more likely to have a lower annual income (238,000-324,000 SEK: aRRR 0.51, 95% CI 0.39-0.77; 325,000 SEK or more 0.36; 0.25-0.58) compared with individuals without AD. These results suggest that AD implies an increased prevalence of comorbid mental conditions and an adverse impact on academic achievement and work. These adverse associations increase substantially for patients with severe AD and comorbid asthma.